Gadara, Jordanien: Forschung und Capacity Building - Bührig, Claudia (e-Forschungsberichte des DAI, 2023)
During the last four years, the research focus of the German Archaeological Institute’s Orient Department in Gadara/Umm Qays has been expanded to exploring the environs in relation to the ancient city complex as well as the settlement and climate development since the Stone Age. In addition to that, a specific emphasis is put on addressing questions of preserving the ancient remains and their presentation for cultural tourism and for local visitors. New research of the ancient town of Gadara’s surroundings provided evidence of palaeolithic, neolithic and early Islamic settlement traces and also the find of two large, out-of-town sanctuaries from the late Augustan/early Roman era. The survey-area is currently part of the new ‚Yarmouk Nature Reserve‘. For the first time, up-to-date findings of archaeological research are integrated in the concept of the nature reserve and put into action in the form of guided tours under the slogan of „Research and Secure“. This includes the participation of local schools as an important part of the project’s didactic aspect as well as the sustainable development of cultural tourism.